2021
DOI: 10.1093/gbe/evab133
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Sensitivity of Primates: Recurrent and Episodic Positive Selection in Hair Cells and Stereocilia Protein-Coding Genes

Abstract: The large spectrum of hearing sensitivity observed in primates results from the impact of environmental and behavioral pressures to optimize sound perception and localization. Although evidence of positive selection in auditory genes has been detected in mammals including in Hominoids, selection has never been investigated in other primates. We analyzed 123 genes highly expressed in the inner ear of 27 primate species and tested to what extent positive selection may have shaped these genes in the order Primate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 102 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…This suggests that although positive selection likely played a role in the initial evolution of these proteins in vertebrate evolution, they have been evolving primarily neutrally (or near-neutrally) since the divergence of most modern vertebrates. Additionally, although there is evidence of positive selection acting on CDH23 and PCDH15 ( Shen et al 2012 ; Moreira et al 2021 ; Trigila et al 2021 ), the sites identified are not found at the CDH23–PCDH15 interface.…”
Section: Discussionmentioning
confidence: 88%
“…This suggests that although positive selection likely played a role in the initial evolution of these proteins in vertebrate evolution, they have been evolving primarily neutrally (or near-neutrally) since the divergence of most modern vertebrates. Additionally, although there is evidence of positive selection acting on CDH23 and PCDH15 ( Shen et al 2012 ; Moreira et al 2021 ; Trigila et al 2021 ), the sites identified are not found at the CDH23–PCDH15 interface.…”
Section: Discussionmentioning
confidence: 88%
“…For example, a high-throughput phylogenetic analysis reported that 13% of inner ear expressed genes showed signatures of positive selection in mammals, compared to nonmammalian vertebrates, both in sensory and nonsensory inner ear cells [37]. Moreover, positive selection in inner-ear-expressed genes has also been reported within mammalian branches [38][39][40][41][42][43][44]. In addition, instances of parallel and/or convergent evolution between echolocating bats and whales have been identified in hearing-related genes [38,40,[45][46][47][48][49][50][51], potentially reflecting distinct environmental demands.…”
Section: Protein Coding Changes In Inner Ear Genesmentioning
confidence: 99%
“…Numerous instances of molecular evolutionary processes have been described for hair bundle proteins (Table 1). Genes encoding proteins constitutive of stereocilia bundles have been described under positive selection in the lineage leading to mammals [37,57], as well as in different mammalian branches (primates [43]; echolocating whales [38,41]; echolocating bats [38]; and mole rats [44,58,59]). These include proteins localised at ankle links and stereocilia rootlets, along the stereocilia shaft, at the stereocilia tips and on the tip links (Figure 2).…”
Section: Hair Bundles and Mechanotransductionmentioning
confidence: 99%
See 1 more Smart Citation